2020
DOI: 10.2147/opth.s238740
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rapid Structural and Functional Improvements with the 0.19 mg Fluocinolone Acetonide Intravitreal Implant for Patients with DME and Low Visual Acuity: 6-Month Data from the UAE</p>

Abstract: Purpose: The 0.19 mg fluocinolone acetonide (FAc) intravitreal implant is approved in the United Arab Emirates (UAE) for treating diabetic macular edema (DME) in patients previously treated with a course of corticosteroids and that did not have a clinically significant rise in intraocular pressure (IOP). This ongoing study is assessing its effectiveness and safety in pseudophakic patients with DME in clinical practice from a single center in the UAE. Methods: A retrospective, ongoing 6-month audit study (NCT03… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…In this retrospective, real-world study, a single injection of the FAc implant demonstrated rapid improvements in BCVA and CMT that were maintained at Month 24 and, in those studied, sustained up to Month 36. These findings support those previously reported 25, 26 , and describe the longevity of the effectiveness of the FAc implant in a real-world setting. The long-term safety of the FAc implant, as assessed by IOP, was consistent with previous reports and with corticosteroid class effects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this retrospective, real-world study, a single injection of the FAc implant demonstrated rapid improvements in BCVA and CMT that were maintained at Month 24 and, in those studied, sustained up to Month 36. These findings support those previously reported 25, 26 , and describe the longevity of the effectiveness of the FAc implant in a real-world setting. The long-term safety of the FAc implant, as assessed by IOP, was consistent with previous reports and with corticosteroid class effects.…”
Section: Discussionsupporting
confidence: 92%
“…24 The 6-and 12-month outcomes of this study, which showed rapid structural and functional improvements that were maintained to 12 months, have previously been described. 25,26 The objective of this study was to assess the effectiveness and safety of the FAc implant at 24-and 36-months in patients with DME and a pseudophakic lens treated in the UAE.…”
Section: Introductionmentioning
confidence: 99%
“…However, that being said, there are a growing number of studies that report outcomes with the DEX implant [6][7][8][9][10][11] and some that even report the use of a FAc implant after prior therapy with DEX implants, in both vitrectomised [22][23][24] and non-vitrectomised eyes. 25,26 Others have also compared outcomes achieved with the FAc implant after prior therapy with anti-VEGF. 25 Few studies report a standardised approach to changing therapy, as studies seem to report outcomes in patients that have been heavily pre-treated before being treated with the FAc implant.…”
Section: Discussionmentioning
confidence: 99%
“…These were a series of small case studies from around the world, in which the findings were remarkably consistent, with most showing improvements in VA and reductions in central retinal thickness (CRT). [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Augustin presented the 3-year results from a German retrospective study (Retro-IDEAL) involving 81 eyes (63 patients) and showed improvements in mean VA at month 6 (+ 4.6 letters) were maintained to year 2 (+ 4.3 letters) before declining slightly at year 3 (+ 2.6 letters). 34…”
Section: Real-world Data Setsmentioning
confidence: 99%
“…The consistent reporting of improvements in VA and retinal anatomy by numerous centres at the ARVO 2018 Annual Meeting 32,36,38,43,45,46 is testimony to the value of this therapy in the treatment of persistent or recurrent DMO. 30,31,34,35,37,42 In addition, emerging evidence shows that patients with DMO, who were insufficiently responsive to intravitreal anti-VEGF drugs, dexamethasone implants and/or focal laser therapy, experienced additional improvements in function after administration of the FAc implant, 45 which raises the important question whether current use of the FAc implant in clinical practice (that is, once DMO has been defined as persisting or recurring after treatment) is optimal.…”
Section: Expert Opinion and Conclusionmentioning
confidence: 99%